Design of Work Instruction (WI) Electronic Workbench-Assisted Electrical Measuring Devices to Improve the Internship Concept of Students in Basic Electronic II Course - Islahudin Islahudin; Johri Sabaryati; Zulkarnain Zulkarnain; Soeharto Soeharto (STKIP Singkawang, 2020)
Basic electronic II course must be supported by software-based virtual laboratory, one of which is to design work instructions (WI) of electrical measuring devices. The objectives of this research was to determine the extent of the influence of the design of work instruction (WI) electronic workbench-assisted electrical measuring devices on improving the internship concept of students in basic electronic II course. The sampling technique waspurposive sampling. The population of this research were all physics studentFaculty of Training Teacher and Education University of MuhammadiyahMataram. The research sample was a class of 2018 students who were took Basic Electronic II course. The research design used was one group pre-test post-test design where the sample was given a pre-test (initial test) before the first treatment and a post-test (final test) at the end of learning. The data analysis technique used was pre-test and post-test with the influence test formula or the t-test at a confidence level of 95%. The improvement in understanding of the internship concepts before and after using work instructions (WI) was calculated using the normalized reinforcement test (N-Gain). The result showed the tcount (= 5,017)>ttable (= 2,365) was at a confidence level of 95%, so that the alternative hypothesis (Ha) was accepted. The improvement in understanding of the internship concept using work instructions (WI) ElectronicWorkbench-assistedelectrical measuring devices was indicated by N-Gain of 0,441, so that it lies in the medium category. Based on the results of the research, it can be concluded that there was a significant influence on the use of the design of work instruction (WI) electronic workbench-assistedelectrical measuring devices on improving of the internship concept of students in the Basic Electronic II course.